A postmodern attitude of Law (Eco and Koskenniemi applied to Constitutional Law) - Gallegos Herrera, Daniel Eduardo (2019)
In this article it’s proposed to take a postmodern attitude toward Law –in general–and specifically toward constitutional law. Based on Umberto Eco’s description of the postmodern, identifiable as a way of revisiting the past in use of irony, the article goes on to identify four ways of operating in art: neoclassicism, romanticism, realism and avant-garde, with regulatory and political approximations and idealist and skeptical attitudes, regarding the law, which Martti Koskenniemi highlights in his work. The work identifies his proposal of a culture of formalism with the postmodern attitude of talking about law in the era of lost innocence, and extending it to a field different from the one in which it was conceived: constitutional law.